Bondi–Hoyle–Lyttleton accretion in supergiant X-ray binaries: stability and disc formation. Issue 4 (25th July 2019) - Xu, Wenrui; Stone, James M
Abstract: We use 2D (axisymmetric) and 3D hydrodynamic simulations to study Bondi–Hoyle–Lyttleton accretion with and without transverse upstream gradients. We mainly focus on the regime of high (upstream) Mach number, weak upstream gradients, and small accretor size, which is relevant to neutron star accretion in wind-fed supergiant X-ray binaries (SgXBs). We present a systematic exploration of the flow in this regime. When there are no upstream gradients, the flow is always stable regardless of accretor size or Mach number. For finite upstream gradients, there are three main types of behaviour: stable flow (small upstream gradient), turbulent unstable flow without a disc (intermediate upstream gradient), and turbulent flow with a disc-like structure (relatively large upstream gradient). When the accretion flow is turbulent, the accretion rate decreases non-convergently as the accretor size decreases. The flow is more prone to instability and the disc is less likely to form than previously expected; the parameters of most observed SgXBs place them in the regime of a turbulent, disc-less accretion flow. Among the SgXBs with relatively well-determined parameters, we find OAO 1657−415 to be the only one that is likely to host a persistent disc (or disc-like structure); this finding is consistent with observations.